Pandangan Al-Qur’an tentang kesabaran: Studi terhadap beberapa ayat tentang sabar - Siregar, Juliadi Rahmad (Maliki Interdisciplinary Journal, 2025)
Patience is one of the main values in Islamic teachings that holds a high position in the Qur’an. This concept is not limited to a passive attitude in facing trials, but also includes perseverance in carrying out obedience, restraining oneself from sinful acts, and facing various life challenges. This paper outlines the meaning of patience according to the Qur’an, the types of patience as mentioned in several verses, and its virtues both from spiritual and social aspects. In addition, this discussion also demonstrates the relevance of patience in the context of modern life, which is full of stress, where patience has a close correlation with psychological concepts such as resilience and emotional stability. Thus, the value of patience in the Qur’an proves to be not only theological but also contributes significantly to shaping character and mental resilience of individuals today.